2017
DOI: 10.18869/acadpub.ibj.21.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Candidates against Nontypeable Haemophilus influenzae: a Review

Abstract: Nonencapsulated, nontypeable Hemophilus influenzae (NTHi) remains an important cause of acute otitis and respiratory diseases in children and adults. NTHi bacteria are one of the major causes of respiratory tract infections, including acute otitis media, cystic fibrosis, and community-acquired pneumonia among children, especially in developing countries. The bacteria can also cause chronic diseases such as chronic bronchitis and chronic obstructive pulmonary disease in the lower respiratory tract of adults. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Efforts to develop a successful vaccine against NTHi are ongoing, with several antigenic virulence factors that contribute to the early stages of bacterial colonization under consideration as potential vaccine candidates (11)(12)(13). Several proteins are under investigation as vaccine candidates (11,14), including fimbriae (OMP P5-homologous fimbriae (15)), outer membrane proteins (OMPs) (P2, P6) (16,17), transferrin binding proteins (TbpB) (18), protein D (19), PilA (major subunit of type IV pili) (20), Hia (21), Hap (22), and HMW1/2 (14,23). However, vaccine development is impeded by the high variability and heterogeneity of NTHi, especially of their surface molecules (13,24).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to develop a successful vaccine against NTHi are ongoing, with several antigenic virulence factors that contribute to the early stages of bacterial colonization under consideration as potential vaccine candidates (11)(12)(13). Several proteins are under investigation as vaccine candidates (11,14), including fimbriae (OMP P5-homologous fimbriae (15)), outer membrane proteins (OMPs) (P2, P6) (16,17), transferrin binding proteins (TbpB) (18), protein D (19), PilA (major subunit of type IV pili) (20), Hia (21), Hap (22), and HMW1/2 (14,23). However, vaccine development is impeded by the high variability and heterogeneity of NTHi, especially of their surface molecules (13,24).…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by the prediction of the location of the highly antigenic epitopes within the cellular structure and docking of selected epitopes with common human allele DRB1*0101. Immunological studies revealed the detection of antibodies against OMPs and LPSs in human serum, thereby, indicating them to be ideal candidates for the activation of humoral immunity hence making them excellent candidates for vaccine development (Behrouzi et al 2017). In the present study, focus was on the prioritization of the outer membrane proteins as vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…These factors, therefore, stress the need for designing and developing effective vaccine candidates against the bacterial strains ( Ulanova et al 2012;Behrouzi et al 2017). Of the various immunogenic biomolecular components, utilizing outer membrane proteins, can serve as an effective candidate for vaccine development (Van Eldere et al 2014).…”
Section: R a F Tmentioning
confidence: 99%
“…In 1931, Avery and Goebel first reported that the conjugation of capsular polysaccharides from Type III pneumococcus to the carrier protein could elicit the production of polysaccharide‐specific IgG antibodies and the long‐lasting immune response . Since then, a similar principle has been successfully applied to various bacteria such as Neisseria meningitidis , Haemophillus infuenzae type b (Hib), and Salmonella enterica serovar typhi . The extensively‐used carrier proteins include tetanus toxoid (TT), diphtheria toxoid (DT), diphtheria toxin derivative (CRM197), keyhole limpet hemocyanin (KLH), bovine serum albumin (BSA), human serum albumin (HSA) and so on.…”
Section: Synthetic Carbohydrate‐based Vaccinesmentioning
confidence: 99%